Analysis of Critical Thinking Skills of Grade VIII Students in SMP Negeri 1 Gunungsitoli Idanoi In Mathematics Learning - Kalebi Rahmat Esa Gea; Sadiana Lase (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the observations of researchers at SMP Negeri 1 Gunungsitoli Idanoi, which is still found that students do not like to study mathematics, sometimes this lesson is a difficult lesson both in material and in learning so that it causes the level of critical thinking of students in solving math problems is still lacking. This study aims to describe the level of critical thinking skills of students, especially class VIII at SMP Negeri 1 Gunungsitoli Idanoi, using descriptive qualitative research methods: research that describes variables as they are supported by data generated from actual circumstances. Based on the research results, the average level of students' critical thinking is 47.39 with the average acquisition of students' critical thinking skills based on indicators obtained: Interpretation indicators (60.58), Analysis indicators (55.29), Evaluation indicators (35.58), and Inference indicators (53.85). Thus, based on the average value of students' critical thinking skills, it is obtained that the level of critical thinking of students is still low. Critical thinking is not easy, but critical thinking skills can be learned and trained.